2016
DOI: 10.1101/lm.042218.116
|View full text |Cite
|
Sign up to set email alerts
|

Ecologically relevant neurobehavioral assessment of the development of threat learning

Abstract: As altricial infants gradually transition to adults, their proximate environment changes. In three short weeks, pups transition from a small world with the caregiver and siblings to a complex milieu rich in dangers as their environment expands. Such contrasting environments require different learning abilities and lead to distinct responses throughout development. Here, we will review some of the learned fear conditioned responses to threats in rats during their ontogeny, including behavioral and physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 246 publications
0
4
0
Order By: Relevance
“…To test this idea, in this article, we searched for AMs in an existing dataset of USVs emitted during a Pavlovian fear conditioning experiment 20 , 21 , in which an aversive unconditioned stimulus (US = foot-shock) was presented following a neutral conditioned stimulus (CS = peppermint odour cue). Fear conditioning is widely used in studies of memory and associative learning 22 25 . The strength of the fear memory is commonly assessed using overt behaviour analysis, such as freezing responses.…”
Section: Introductionmentioning
confidence: 99%
“…To test this idea, in this article, we searched for AMs in an existing dataset of USVs emitted during a Pavlovian fear conditioning experiment 20 , 21 , in which an aversive unconditioned stimulus (US = foot-shock) was presented following a neutral conditioned stimulus (CS = peppermint odour cue). Fear conditioning is widely used in studies of memory and associative learning 22 25 . The strength of the fear memory is commonly assessed using overt behaviour analysis, such as freezing responses.…”
Section: Introductionmentioning
confidence: 99%
“…Odor fear conditioning has been well characterized during ontogeny and this literature has shown that fear learning emerges in rat pups around PN10 and is caused by the recruitment of the amygdala during the odor–shock conditioning (Sullivan et al 2000a; Moriceau et al 2006; Raineki et al 2009; Boulanger-Bertolus et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that while we described important differences in the emission of USV between infancy and adulthood, the consequences of USV emission on the infant brain remains entirely unknown at this point. Aversive events that induce USV have drastically different consequences at these two stages of development, and their memories also differentially affected the animal’s subsequent behavior [ 159 , 160 ]. The 22-kHz rat vocalizations present an evolutionary counterpart to human crying [ 161 ], and human infant crying and rat pup USV have been suggested to share some similarities [ 72 ].…”
Section: Usv Emission Impacts Brain Activitymentioning
confidence: 99%